Mating system and population analysis of the broad-snouted caiman (Caiman latirostris) using microsatellite markers - Amavet, Patricia Susana (2012)
The knowledge about reproductive strategies of a species contributes to their conservation. Multiple paternity is a reproductive behavior increasing effective population size, which could increase genetic diversity particularly in populations submitted to bottlenecks events. In Argentina, wild populations of Caiman latirostris are subject of a management plan devoted to their preservation and sustainable utilization based on its commercial interest. This program started in response to the evident numeric reduction of the populations, as a consequence of hunting pressure and habitat modification; it had a remarkable success in population recovery allowing the commercial use of C. latirostris. Data on reproductive behavior of C. latirostris are limited because mating occurs in the water and the information about their genetic diversity is scarce too. Our specific aims were to study the mating system and population genetic structure applying microsatellite markers in twelve C. latirostris families. The obtained results showed highly significant difference among populations and a lack of correspondence between geographical distance and genetic differentiation suggesting that populations of C. latirostris represent unstable metapopulations. In the paternity analysis was detected more than one father in two nests, which could be explained by capacity of storage sperm, proposed in females of a related species. The behavior of multipaternity could contribute to maintain viable populations of C. latirostris, since the maintenance of genetic variability within populations could help increase their capacity to respond to selective pressure. Further studies employing genetic and behavioral framework are needed to better understand the reproductive biology of C. latirostris.